ANALYSIS OF LOW VACUUM MICROWAVE DISCHARGE EXCITING CONDITIONS IN RESONATOR TYPE PLASMATRON - S. I. Madveika; S. V. Bordusau; M. S. Lushakova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The efficiency of a cavity microwave resonator using for getting large volume (more than 4000 cm3) low vacuum plasma for group treatment of products in the microelectronics technology has been evaluated. The results showed that the value of electric field breakdown intensity about E0 ≈ 110 V/cm in a resonator system for low vacuum can be already achieved at a microwave power higher than 50 W. As far as the conditions of exciting and maintaining the microwave plasma for technological application are concerned, the conditions of preserving resonating properties at exciting plasma with a volume of 9000 cm3 in resonator and in case of placing a various number of silicon wafers in the microwave discharge have been analyzed. The results of the calculations show that at the presence of plasma the quality factor of the cavity resonator change caused by its partial loading with semiconductor wafers leads to the decrease of resonator’s total quality factor by 2,5 times. In order to excite microwave discharge at total quality factor of loaded resonator Q ≈ 200, the value E0 ≈ 110 V/cm can be provided with using microwave magnetron of medium power level ( Pgen ≈ 650 W).